Military Realism : The Logic and Limits of Force and Innovation in the U.S. Army - Campbell, Peter P. (Book collections on Project MUSE., 2019)
"After the Vietnam War, the U.S. Army considered counterinsurgency (COIN) a mistake to be avoided. Many found it surprising, then, when setbacks in recent conflicts led the same army to adopt a COIN doctrine. Scholarly debates have primarily employed existing theories of military bureaucracy or culture to explain the army's re-embrace of COIN, but Peter Campbell advances a unique argument centering on military realism to explain the complex evolution of army doctrinal thinking from 1960 to 2008. In five case studies of U.S. Army doctrine, Campbell pits military realism against bureaucratic and cultural perspectives in three key areas--nuclear versus conventional warfare, preferences for offense versus defense, and COIN missions--and finds that the army has been more doctrinally flexible than those perspectives would predict. He demonstrates that decision makers, while vowing in the wake of Vietnam to avoid COIN missions, nonetheless found themselves adapting to the geopolitical realities of fighting "low intensity" conflicts. In essence, he demonstrates that pragmatism has won out over dogmatism. At a time when American policymakers remain similarly conflicted about future defense strategies, Campbell's work will undoubtedly shape and guide the debate"--